2019
DOI: 10.3390/s19102272
|View full text |Cite
|
Sign up to set email alerts
|

A Resonant Pressure Microsensor with the Measurement Range of 1 MPa Based on Sensitivities Balanced Dual Resonators

Abstract: This paper presents a resonant pressure microsensor with the measurement range of 1 MPa suitable for the soaring demands of industrial gas pressure calibration equipment. The proposed microsensor consists of an SOI layer as a sensing element and a glass cap for vacuum packaging. The sensing elements include a pressure-sensitive diaphragm and two resonators embedded in the diaphragm by anchor structures. The resonators are excited by a convenient Lorentz force and detected by electromagnetic induction, which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Pressure microsensors have been explored for various potential applications, such as industrial control, healthcare, medical testing, aerospace, meteorology, and environmental monitoring [9][10] [11]. Different sensing mechanisms and designs have been used for the detection of air-pressure, such as capacitive, piezoelectric, piezoresistive, and resonant [12] [13] [14][15] [16]. Resonant pressure micro-sensors have the advantage of digital frequency output, which can be measured with high precision using simple electronic circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure microsensors have been explored for various potential applications, such as industrial control, healthcare, medical testing, aerospace, meteorology, and environmental monitoring [9][10] [11]. Different sensing mechanisms and designs have been used for the detection of air-pressure, such as capacitive, piezoelectric, piezoresistive, and resonant [12] [13] [14][15] [16]. Resonant pressure micro-sensors have the advantage of digital frequency output, which can be measured with high precision using simple electronic circuits.…”
Section: Introductionmentioning
confidence: 99%
“…4d. The dimension of the resonant pressure sensor chip is only 4.7 mm × 5.7 mm, which is much smaller than the reported resonant pressure sensors 6,14 , in Fig. 4e.…”
Section: Micromachining Processmentioning
confidence: 77%
“…These capacitive detection-based resonant pressure sensors showed that the change in the detection capacitance was extremely small, requiring a signal amplifier circuit with an extremely large amplification factor; meanwhile, the crosstalk between an excitation comb and capacitance detection comb was hard to eliminate 12 . Electromagnetic detection-based resonant pressure sensors have been comprehensively researched by Li et al 11 and Lu et al 14 ; these sensors have a total accuracy that is >0.01% FS. However, external magnets must be mounted on the sensors, and thus the sensors have large package sizes and poor temperature sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The reported data showed that the sensitivity was 1.8 Hz/kPa under a measurement range of 10 kPa to 1 MPa. Furthermore, our previous studies focused on several types of resonant pressure sensors with pressure measurement ranges over 500 kPa, such as Lu (2019) [ 32 ], Yan (2019) [ 33 ] and Xiang (2020) [ 34 ], with s maximal value of 2 MPa.…”
Section: Introductionmentioning
confidence: 99%